I.I. Hemnitser and German literature - N. Zhatkin, Dmitry (2019)
Objectives: In the last decades such marginal phenomenon as works of Russian authors written in European, languages attract considerable interest of researchers. After Yu.M. Lotman, E.P. Grechanaya's, works devoted to Russian Literature in French, there was a number of researches of German-language works of such Russian writers as V.A. Zhukovsky, A.K. Tolstoy, K.K. Pavlova, E.I. Guber, E.B. Kulman, etc. In this article the task to reveal features of works of the Russian poet I.I. Hemnitser (1745–1784) is set in the context of Russian-German literary and historical and cultural communications of the last third of the 18th century. Methods: Poems in German written by I.I. Hemnitser, his fables created under the influence of Christian Fyurkhtegott Gellert's creative works became the material for the analysis. Comparative-historical and comparative and typological methods and also complex analysis were used in the work. Findings: The detailed analysis of ideological and thematic contents of works in German of the Russian poet is carried out. The specific features of I.I. Hemnitser’s creative manner are established. Special attention is paid to a question of interpretation of fable, epigrammatic and lyrical works of the poet in aspect of international literary relations and historical and literary traditions. Novelty: The revealed features of I.I. Hemnitser’s works in German allow to say that during an era of the increased influence on the Russian society of the French literature and French (a century of Catherine II) I.I. Hemnitser was one of the few Russian writers in the works of whom Russian-German literary and historical and cultural interaction was systemically presented. His fables became transfers, free translations of Ch.-F. Gellert’s works.